Chin Tremors Associated with Paroxetine in a Patient with Pancreatic Adenocarcinoma - John, Preethi; McConnell, Kathleen; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
Context There have been many cases of medication-induced tremors. We report a patient who developed significant chin tremors after the administration of paroxetine. Case report A 68-year-old Vietnamese female with a past medical history including GIST and pancreatic cancer status post Whipple procedure and six months of adjuvant chemotherapy with gemcitabine presented with symptoms of anxiety for which she was treated with paroxetine. Within 2 weeks she developed chin tremors which resolved after paroxetine was discontinued. Conclusions To our knowledge, this is the first case report of a temporary chin tremor associated with paroxetine. The exact mechanism of this phenomenon is unclear. However, it has been suggested that movement disorders such as chin tremors may be related to elevated serotonin levels causing an inhibition of central dopamine. Image: Statue of Jumbo (Tufts University’s official mascot) on the north side of Barnum Hall at Tufts University campus. Medford, MA, USA.